Bridging Learning Gaps: A Needs Analysis for Developing Calistung Workbooks for Second Grade Students - Rahmania Zen; Djoko Susanto; Luthfiya Fathi Pusposari (Educazione: Journal of Education and Learning, 2025)
This study examines the need to develop dedicated literacy and numeracy instructional materials to strengthen the cognitive skills of second grade primary school students. The study specifically focuses on Calistung (an acronym for membaca, menulis, and berhitung, referring to reading, writing, and basic arithmetic), which represents the core foundational competencies in Indonesian primary education. Using a qualitative descriptive approach, data were gathered through classroom observations, in depth teacher interviews, and documentation of learning activities and student performance. The findings reveal noticeable variation in students’ abilities in reading, writing, and arithmetic, while existing thematic textbooks provide limited opportunities for structured and repeated practice. Teachers consistently highlighted the importance of materials that are clear, visually engaging, developmentally appropriate, and supported by concrete examples and progressively organized exercises. The study also shows that students respond more actively to contextual and illustrated learning tasks, which help them connect abstract concepts to familiar experiences. Based on these insights, the development of a structured Calistung workbook is considered essential to support stepwise skill acquisition, encourage independent learning, and reduce reliance on constant teacher assistance. Such materials can foster confidence, sustain engagement, and promote gradual mastery of foundational skills. This research contributes to primary education by offering a practical framework for designing instructional resources that align with students’ cognitive development and classroom realities, while addressing persistent gaps in early literacy and numeracy learning.